Recurrence Relations – Obtaining Binomial Coefficients Without Counting Subsets

binomial-coefficientsrecurrence-relations

I want to obtain the formula for binomial coefficients in the following way: elementary ring theory shows that $(X+1)^n\in\mathbb Z[X]$ is a degree $n$ polynomial, for all $n\geq0$, so we can write

$$(X+1)^n=\sum_{k=0}^na_{n,k}X^k\,,\ \style{font-family:inherit;}{\text{with}}\ \ a_{n,k}\in\mathbb Z\,.$$

Using the fact that $(X+1)^n=(X+1)^{n-1}(X+1)$ for $n\geq1$ and the definition of product of polynomials, we obtain the following recurrence relation for all $n\geq1$:

$$a_{n,0}=a_{n,n}=1;\ a_{n,k}=a_{n-1,k}+a_{n-1,k-1}\,,\ \style{font-family:inherit;}{\text{for}}\ k=1,\dots,n-1\,.$$

I want to know if there is a way to manipulate this recurrence in order to obtain directly the values of the coefficients $a_{n,k}$, namely $a_{n,k}=\binom nk=\frac{n!}{k!(n-k)!}$.

Note that the usual approach via generating functions definitely will not work, at least in the spirit of my question, because this method only works when we do know in advance the coefficients of the generating function (either by the "number of $k$-subsets" argument, or Maclaurin series for $(X+1)^n$, or anything else) and this is precisely what I intend to avoid.

This question is closely related to a recent question of mine. Actually the same question, with Bernoulli numbers instead of binomial coefficients.

EDIT

I do not consider as a valid manipulation the following "magical" argument: 'the sequence $(b_{n,k})$ given by $b_{n,k}=\frac{n!}{k!(n-k)!}$ obeys the same recurrence and initial conditions as $(a_{n,k})$, so $a_{n,k}=b_{n,k}$ for all $n,k$. How did you obtain the formula for the $b_{n,k}$ at the first place? Okay, you can go through the "counting subsets" argument, but this is precisely what I don't want to do. The same applies to my related question about Bernoulli numbers.

Best Answer

A simple-minded approach is to solve the two variable recurrence relation iteratively, that is, knowing $a_{n,0}$ find $a_{n,1}$, then $a_{n,2}$, etc.

We must have
$$\begin{eqnarray*} a_{n,1} &=& a_{n-1,1}+a_{n-1,0} \\ &=& a_{n-1,1}+1, \qquad a_{1,1}=1. \end{eqnarray*}$$ This is a one variable recurrence relation of the form $$b_n = b_{n-1}+1, \qquad b_1 = 1.$$ This can be solved by the usual methods. We find $a_{n,1} = n.$

Next we have $$\begin{eqnarray*} a_{n,2} &=& a_{n-1,2}+a_{n-1,1} \\ &=& a_{n-1,2}+n-1, \qquad a_{2,2}=1. \end{eqnarray*}$$ This is another simple recurrence relation. We find $a_{n,2} = n(n-1)/2.$

At the next step, $$\begin{eqnarray*} a_{n,3} &=& a_{n-1,3}+a_{n-1,2} \\ &=& a_{n-1,3} + \frac{1}{2}(n-1)(n-2), \qquad a_{3,3}=1. \end{eqnarray*}$$ This implies $a_{n,3} = n(n-1)(n-2)/6.$

This process can be repeated to build up $a_{n,k}$ for any $k$. At some point a pattern will be noticed and the principle of induction can be applied.

Related Question